The Role of School Administrators in Promoting Active Teachers of Extra-large Size Secondary Schools in Lamphun Province under the Lampang – Lamphun Secondary Educational Service Area Office - Boontachan, Tanakrit; Wangcham, Sangwan (Journal of Humanities and Social Sciences, Rajapruk University, 2024)
The Objective of this research were to 1) study the role of school administrators in promoting Active Teachers and 2) to study the guidelines to develop the role of school administrators in promoting Active Teachers of extra-large size secondary schools in Lamphun Province under Lampang-Lamphun Secondary Educational Service Area Office. The population included 320 teachers and school administrators and used a simple random sampling method, proportional to the number of personnel in each school, which had a sample of 179 people which included 7 school administrators and 172 teachers. The tools used were questionnaires and interviews, basic statistics, percentage, average ( ), standard deviation (S.D.), and frequency. The results of the research revealed that the role of school administrators in promoting Active Teachers, in overall, was at a high level ( = 4.21,S.D. = 0.63). The guidelines for developing the role of school administrators in promoting Active Teachers were as follows; the schools should formulate policies and put them into practice, create participation, motivate teachers and personnel to use technology in teaching management, develop internet systems in schools, train teachers, develop various applications in teaching, provide knowledge in the information system to students continuously, find specialist to train teachers, support materials, provide learning resources to facilitate the learning of learners by focusing on the needs and promoting excellence, develop the potential of learners in all areas, arrange a meeting to exchange knowledge from teaching practices every month, analyze the internal and external environments to determine the direction of action to achieve the objectives according to the goals, analyze the needs, planning and implementing facilities maintenance, monitoring, evaluation, improvement and development of facilities.